Market Higiene and Sanitation Implementation Study (Case Study: Demangan Market) - Sardi Sardi; Ceria Nur Utami Novania Putri (Universitas Sarjanawiyata Tamansiswa, 2025)
Demangan Market is one of the public facilities that plays an important role in fulfilling the daily needs of the community. Market activities involve many people, both sellers and buyers, making it a center of social and economic interaction. However, poor market sanitation conditions can increase the risk of contamination exposure and health problems for both visitors and traders. This study aims to analyze the implementation of hygiene and sanitation at Demangan Market, Yogyakarta, based on several assessment parameters and clean water quality indicators. The research employed a quantitative descriptive method by conducting assessments using a market inspection form that includes aspects such as market location, building conditions, sanitation facilities, Clean and Healthy Living Behavior (PHBS), lighting, noise levels, and safety. Water samples were collected from two well points and tested for pH, Total Dissolved Solids (TDS), dissolved oxygen (DO), and iron content (Fe). The research instruments consisted of observation sheets, literature reviews, documentation studies, and laboratory examinations, with data analysis performed using Microsoft Excel. The results indicate that Demangan Market is categorized as less healthy, with an achievement score of 68.22%, which is below the Minimum Main Criteria (≤70%). Meanwhile, the water quality test results show that all samples meet the clean water quality standards based on Ministry of Health Regulation No. 2 of 2023. The six water samples revealed varying results, with pH values ranging from 6.8 to 7.0, TDS values ranging from 151 to 260 mg/L, dissolved oxygen levels ranging from 5.3 to 6.7 mg/L, and iron content (Fe) of 0.00168 mg/L. Based on these findings, it is recommended that the Health Department conduct counseling programs, monitoring, and trader training to improve the implementation of hygiene and sanitation practices, aiming to achieve a Healthy Demangan Market.